The Trypanocidal Activity of Naphthoquinones: A Review - Solange Lisboa de Castro; Antônio Ventura Pinto (Molecules, 2009)
Naphthoquinones are compounds present in several families of higher plants. Their molecular structures confer redox properties, and they are involved in multiple biological oxidative processes. In folk medicine, especially among Indian populations, plants containing naphthoquinones have been employed for the treatment of various diseases. The biological redox cycle of quinones can be initiated by one electron reduction leading to the formation of semiquinones, unstable intermediates that react rapidly with molecular oxygen, generating free radicals. Alternatively, the reduction by two electrons, mediated by DT-diphorase, leads to the formation of hydroquinone. Lapachol, α-lapachone and β-lapachone, which are isolated from the heartwood of trees of the Bignoniaceae family, are examples of bioactive naphthoquinones. In this review, we will discuss studies investigating the activity of these natural products and their derivatives in the context of the search for alternative drugs for Chagas disease, caused by Trypanosoma cruzi, a neglected illness that is endemic in Latin America.